HRD Practices in Co-operative Sugar Mills in North Coastal Andra Pradesh - Krishna, B.Murali; Jagarao, Malla (International Research Journal of Management, IT & Social Sciences, 2015)
Human resources are considered as most valuable strategic assets to the organization. The success of any organization depends on efficient use of human resources in the organization. This paper aims to analyze the various Human resource development (HRD) practices in co-operative sugar industry in north coastal Andrapradesh. The study measured an evaluation of HRD practices in the sugar industry. A sample of 100 employees from five co-operative sugar mills responded to a questionnaire which measured the evaluation of HRD practices and improve the values. HRD practices like training and development, performance appraisal system, quality of work life and development were positively related to organizational values of humane treatment. However, performance appraisal system, career planning, and contextual analysis variables were negatively associated with values such as trust and creativity. The analysis was limited to existing HRD practices. Further studies are needed on a larger sample to examine why some HRD practices and contextual analysis contributed negatively to organizational values. The result of the study can be useful in designing effective employee development programs that promote cherished organizational values. Little empirical knowledge exists on HRD practices and organizational values linkages in the context of co-operative sugar industry in Andrapradesh. The paper makes a modest attempt to fill the gap.